2014
DOI: 10.1007/s13213-014-0844-9
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state fermentation of coconut kernel-cake as substrate for the production of lipases by the coconut kernel-associated fungus Lasiodiplodia theobromae VBE-1

Abstract: Plant oil-extracted seed-cakes are good fermentation substrates for producing lipases that find application in transesterification of seed oils into biodiesel. This work describes the production of lipases by five lipolytic, oil-seed associated fungi (Aspergillus niger, Chalaropsis thielavioides, Colletotrichum gloeosporioides, Lasiodiplodia theobromae, and Phoma glomerata) by Solid-State Fermentation (SSF) on eight plant oil-seed cakes. The highest lipase activity was from the Coelomycete Lasiodiplodia theobr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Short chain fatty acids are metabolized faster without the need for carnitine transport system . Venkatesagowda et al reported that supplementation of coconut kernel‐cake with mineral salts and coconut oil enhanced the activity of lipase from the fungus Lasiodiplodia theobromae VBE‐1.…”
Section: Discussionmentioning
confidence: 99%
“…Short chain fatty acids are metabolized faster without the need for carnitine transport system . Venkatesagowda et al reported that supplementation of coconut kernel‐cake with mineral salts and coconut oil enhanced the activity of lipase from the fungus Lasiodiplodia theobromae VBE‐1.…”
Section: Discussionmentioning
confidence: 99%
“…The source of nitrogen and the C/N ratio are important parameters of SSF which should be optimized to maximize biomass and enzyme production [9], and thus minimize the cost of the process. Several works have demonstrated that the addition of nitrogen to agro-industrial wastes can improve enzyme production [10][11][12]. The evaluation of nitrogen sources (organic and inorganic) is important, because their use is subject to metabolic versatility, as well as economic implications [13].…”
Section: Introductionmentioning
confidence: 99%
“…Penha et al [121], in their experiment, concluded that pure palm pie was an incomplete substrate for lipase production by A. niger 11T53A14; however, ammonium sulfate solution, as a nitrogen source, was capable of positively influencing lipase production. Salwoom et al [141] analyzed the nutritional factors involved in lipase production by bacterial strains obtained from the soil of Signy Island.…”
Section: Lipase Production: Type Of Fermentation and Nutrientsmentioning
confidence: 99%